Synthesis and Pharmacological Screening of Pyridopyrimidines as Effective Anti‐Diarrheal Agents through the Suppression of Cyclic Nucleotide Accumulation. Issue 4 (8th April 2019) - Zaminelli, Tiago; Magli, Elisa; Frecentese, Francesco; Lescano, Caroline H.; Campos, Rafael; Saccone, Irene; Corvino, Angela; Di Vaio, Paola; Giordano, Flavia; Luciano, Paolo; Fiorino, Ferdinando; Perissutti, Elisa; et al.
Abstract: The increased levels of cyclic nucleotides (cGMP and cAMP) in enterocytes trigger intracellular mechanisms of ion and fluid secretion into the lumen, causing secretory diarrhea. Twelve novel pyridopyrimidines derived from 5‐(3, 5‐bistrifluoromethylphenyl)‐1, 3‐dimethyl‐5, 11‐dihydro‐1H‐indeno[2, 1 : 5, 6]pyrido[2, 3‐d]pyrimidine‐2, 4, 6‐trione (FPIPP) were synthesized and evaluated on intracellular cyclic nucleotide accumulation. All compounds had no effect on either cyclic nucleotide basal levels or on pre‐contracted aortic rings. The metabolic activity and viability in T84 cells, assessed by MTT (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide) and the LDH (lactate dehydrogenase) assays, respectively, were not affected by incubation with the compounds (50 μM). CompoundVI almost abolished cGMP accumulation (94 % inhibition) induced by STa toxin in T834 cells and significantly reduced (69 %) forskolin‐induced cAMP accumulation in Jurkat cells. CompoundVI was active in an in vivo model for diarrhea in rabbits. These results prompted us to perform a microscopic histopathological analysis of intestinal tissues, showing that only compoundVI preserves the intestine without significant pathological changes and with a decreased inflammatory pattern in comparison to FPIPP. In vitro stability test revealed that compoundVI is resistant to oxidation promoted by atmospheric oxygen. Abstract : Stop diarrhea : Twelve novel pyridopyrimidines are synthesized and evaluated for intracellular cyclic nucleotide accumulation. CompoundVI was active in an in vivo model for diarrhea in rabbits. Microscopic histopathological analysis of intestinal tissues showed that only compoundVI preserves intestine, without significant pathological changes and with a decreased inflammatory pattern.